2020
DOI: 10.1111/ejn.14931
|View full text |Cite
|
Sign up to set email alerts
|

Can the occipital alpha‐phase speed up visual detection through a real‐time EEG‐based brain–computer interface (BCI)?

Abstract: Electrical brain oscillations reflect fluctuations in neural excitability. Fluctuations in the alpha band (α,(8)(9)(10)(11)(12) in the occipito-parietal cortex are thought to regulate sensory responses, leading to cyclic variations in visual perception. Inspired by this theory, some past and recent studies have addressed the relationship between α-phase from extra-cranial EEG and behavioural responses to visual stimuli in humans. The latest studies have used offline approaches to confirm α-gated cyclic pattern… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…These effects might be associated with entrainment, in which low-frequency neural oscillations in connection with fluctuations between periods of high and low neural sensitivity to the input and become phase-aligned to the external rhythmic stream such that periods of high sensitivity coincide with on-beat times of rhythmic stimuli ( Jones, 1976 ; Large and Jones, 1999 ; Barnes and Jones, 2000 ; Schroeder and Lakatos, 2009 ; Breska and Deouell, 2016 ). A handful of studies failed to find the rhythmic behavioral benefits ( Benwell et al, 2017 ; Ruzzoli et al, 2019 ; Vigué-Guix et al, 2020 ; Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These effects might be associated with entrainment, in which low-frequency neural oscillations in connection with fluctuations between periods of high and low neural sensitivity to the input and become phase-aligned to the external rhythmic stream such that periods of high sensitivity coincide with on-beat times of rhythmic stimuli ( Jones, 1976 ; Large and Jones, 1999 ; Barnes and Jones, 2000 ; Schroeder and Lakatos, 2009 ; Breska and Deouell, 2016 ). A handful of studies failed to find the rhythmic behavioral benefits ( Benwell et al, 2017 ; Ruzzoli et al, 2019 ; Vigué-Guix et al, 2020 ; Lin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the exact sampling frequencies implicated in cognitive functions often differ between studies and have been shown to depend on the task and/or stimulus characteristics (Chen et al, 2020;Ho et al, 2017;Merholz et al, 2022;Ronconi et al, 2017; also see table in Ruzzoli et al, 2019), which is difficult to reconcile with any simple model of fixed, discrete temporal 'frames' (White, 2018). Additionally, the effect sizes in studies showing periodicity in behavioural or neural measures tend to be small, hence not in line with clear, all-or-nothing frame boundaries (Milton & Pleydell-Pearce, 2016;White, 2018) or utility for real-life applications (Vigué-Guix et al, 2020). Furthermore, the literature suffers from a lack of direct replications, preregistered studies, data, and code sharing (Garrett-Ruffin et al, 2021;Niso et al, 2021;Pavlov et al, 2021), as well as low statistical power (Button et al, 2013).…”
mentioning
confidence: 99%
“…This entrainment proposal rests on the key idea that neural oscillations reflect alternating excitability states (excitation/inhibition) of neuronal ensembles (Başar et al, 2013;Bishop, 1932). While there is some evidence that the phase of ongoing oscillations at the time of sensory stimulation impacts the neural response to that stimulus, as well as subsequent behavioural performance (e.g., Busch et al, 2009;Mathewson et al, 2009;Ten Oever & Sack, 2019; for a review see VanRullen, 2016), this evidence is far from conclusive as several studies have reported null results (e.g., Benwell et al, 2017;O'Hare, 1954;Ruzzoli et al, 2019;Vigué-Guix et al, 2020;Walsh, 1952).…”
mentioning
confidence: 99%